Translation of Sexual Expressions and Their Synonyms in Bared to You Novel as Sexual Discourse - Janis Ramadhanti Saputri; Doni Jaya (Journal of Language and Literature, 2025)
Discourse concerning sexuality in Indonesia is influenced by religion, social norm, and the Pornography Law that governs the circulation of media with explicit sexual content. However, bookstores in Indonesia sell translated novels with explicit sexual scenes. One of such novels is Terbuka Untukmu (2013), the Indonesian translation of Sylvia Day’s Bared to You (2012). This research aims to analyze how the discourse concerning sexuality itself is limited (Foucault, 1972) and how such limitation(s) (Levefere, 1992) influences the translation of sexual expressions and their synonyms in the novel. This research was conducted by applying the corpus-based descriptive analysis approach using Vinay and Darbelnet’s translation procedures (1995). This research found that there were synonymous expressions with differing degree of vulgarity that were translated into the same expressions. Vulgar and neutral expressions were translated into the same expression, and so were vulgar and positive expressions. However, neutral and positive expressions were not translated into the same expression. It can be concluded that the discourse concerning sexuality in the target readers’ society is limited through the usage of the sexual expressions in order to significantly reduce the vulgarity of the expressions which was present in the source text and to minimize the inclusion of female genitalia so that the translation is more acceptable among the target readers. This study will also help in showing English to Indonesian translators the diversity of translating certain sexual expressions in literary translations.